Ezra‐Nehemiah - Talshir, Zipora (Journal of Semitic studies, 2002)
Ezra‐Nehemiah Lester L.Grabbe (Old Testament Readings). RoutledgeLondon 1998x + 209Paperback£14.99 0‐415‐14154‐0 , 1Ben‐Gurion University